Upaya peningkatan pengetahuan masyarakat tentang penyakit filariasis di Desa Kemingking Dalam Kecamatan Taman Rajo - Eti Kurniawati; Putri Sahara Harahap; Ratna Sari Dewi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
ProvinceJambi is one of the filariasis endemic areas. Almost all regencies / cities in Jambi Province have filariasis cases. Cumulatively the number of chronic filariasis cases reported in Jambi Province in 2014 was 375 cases spread across 9 Regencies / Cities with the highest cases in Muaro Jambi District. Based on the results of the 2014 Finger Blood Survey (SDJ), 180 cases of filariasis in Muaro Jambi District were scattered in 13 health centers in 8 sub-districts of 11 sub-districts. With the discovery of new cases as many as 9 cases. And the most cases were in the MuroKumpeh Health Center area of ​​50 cases. Community service activities are carried out with counseling methods and demonstrations related to filariasis and methods of prevention. From the results of the survey it is known that Muaro Jambi Regency is still an endemic filariasis area with an Mf rate of 1.8%. There was an increase in the average knowledge of the community from before and after the socialization of filariasis in the village of KemingkingDalam.